2017
DOI: 10.3390/cosmetics4030034
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenic Activity of Auraptene via ERK-mediated MITF Downregulation

Abstract: Abstract:Auraptene is the most abundant naturally occurring geranyloxycoumarin. It is primarily isolated from plants belonging to the Rutaceae family, many of which, such as citrus fruits, are used as food in many countries. Auraptene is a biologically active secondary metabolite that possesses valuable properties. The aim of this study was to investigate the in vitro inhibitory effects of auraptene on melanogenesis and the enzymes associated with it, such as tyrosinase, tyrosinase-related protein (TRP)-1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent studies have indicated that 200 nM α‐MSH is normally used to stimulate B16F10 melanoma cells. Therefore, we used 200 nM α‐MSH to stimulate B16F10 melanoma cells 13–15 . Further experiments were conducted using these concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that 200 nM α‐MSH is normally used to stimulate B16F10 melanoma cells. Therefore, we used 200 nM α‐MSH to stimulate B16F10 melanoma cells 13–15 . Further experiments were conducted using these concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used 200 nM α‐MSH to stimulate B16F10 melanoma cells. 13 , 14 , 15 Further experiments were conducted using these concentrations. Even when B16F10 melanoma cells were treated with α‐MSH and LFE, there was no significant difference compared with the non‐LFE‐treated group (Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…During our ongoing screening program designed to identify modulators of skin inflammation and melanogenesis from coumarin and its derivatives, we reported that 8-methoxycoumarin increased melanogenesis via the MAPK signaling pathway [ 8 ]. In addition, we identified that auraptene, the most abundant naturally occurring geranyloxycoumarin, possesses anti-melanogenic activity through ERK-mediated MITF downregulation [ 9 ]. Furthermore, we reported that 7,8-dimethoxycoumarin stimulates melanogenesis via MAPK-mediated MITF upregulation and attenuates the expression of IL-6, IL-8, and CCL2/MCP-1 in TNF-α-treated HaCaT cells [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%